Four ways geographic information systems can help to enhance health service planning and delivery for infectious diseases in low-income countries - Brijnath, Bianca; Ansariadi; de Souza, D. (2012)
Focusing specifically on infectious diseases in low-income countries, this paper discusses four ways Geographic Information Systems (GIS) can facilitate health service planning and delivery: (1) deeper insight into where health care services should be located; (2) improved health surveillance and real-time planning for disease control and population health; (3) stronger accountability and evidence-informed dialogue between funders and the service providers and; (4) greater opportunities to translate complex data into more accessible formats which policymakers can quickly interpret and act on. Taking its use beyond just a research instrument, GIS is a way to undertake multidisciplinary work and improve health service planning and delivery.